Use of double J stent in kidney transplantation: a single-center cohort report - Ertugrul, Gokhan; Yanaral, Tumay (Ukrainian Journal of Nephrology and Dialysis, 2019)
Kidney transplantation is the treatment of choice for end-stage kidney disease.The double J stent is commonly used in kidney transplantation.The incidence of urologic complications varies between 0.22 % and 30 %. Ureteral strictures and urinary leakage are the most common urological complications after kidney transplantation. Use of the double J stent can decrease urological complications after kidney transplantation. However, the double J stent can increase urinary tract infections, suprapubic pain and urinary incontinence. This study aimed to evaluate the outcomes of the use of double J stent in kidney transplantation. Methods. Between April 2014 and April 2019 130 patients with the use of double J stent were studied retrospectively at Medipol University Medical Faculty Hospital Organ Transplantation Department, Istanbul, Turkey. In these patients, demographic features, clinical features and urologic complications were evaluated. Results. The mean age of the patients was 38.3 ± 15.6 years. 84 (67 %) patients were males and 46 (33 %) were females. Mean follow-up was 29.1 ± 15 months. Mean double J stent removal time was 31.3 ± 2.2 days. During follow-up, there were no ureteral strictures and urinary leakage. Urinary infections were diagnosed in 5 (3.8 %) patients. Conclusions. Use of double J stent appears to be successful to prevent the urological complications in kidney transplantation.